2015
DOI: 10.1111/nmo.12579
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of mast cells to postoperative ileus in experimental and clinical studies

Abstract: The persistent phase of postoperative ileus (POI) is mediated by inflammatory activation of the resident myeloid immune cell population in the gut wall, likely elicited by neurogenic activation. Mast cells are thought to play a critical role in this inflammatory response and involvement of mast cells in POI has been investigated and described thoroughly in experimental studies. Intestinal manipulation (IM) leads to degranulation of mast cells, resulting in an increase in mast cell proteases in peritoneal fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 60 publications
2
22
0
Order By: Relevance
“…, a correlation between POI and AL was also demonstrated. The current results support the experimental findings that systemic inflammation is important in POI .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…, a correlation between POI and AL was also demonstrated. The current results support the experimental findings that systemic inflammation is important in POI .…”
Section: Discussionsupporting
confidence: 90%
“…In a cross-check analysis, evaluating the data of a randomized controlled trial conducted by Boelens et al [9], a correlation between POI and AL was also demonstrated. The current results support the experimental findings that systemic inflammation is important in POI [21,22]. Over the last 20 years surgical technique [23] and perioperative regimes [24] have evolved and scoring systems for AL have been developed [25,26].…”
Section: Discussionsupporting
confidence: 86%
“…This is due to a time‐ and procedure‐dependent inflammatory response to intestinal handling. Mast cells and damage‐associated molecule patterns are thought to play a critical role in this process by activating macrophages of the bowel muscularis. The actions of mast cells lead to an altered mucosal barrier to luminal bacteria, aspects of which are due to toll‐like receptors that display remarkable interspecies homology.…”
Section: Pathogenesis Of Postoperative Ileusmentioning
confidence: 99%
“…In particular, postoperative ileus (POI) is affecting 10%‐40% of patients undergoing a colorectal resection and is an important clinical determinant of short‐term morbidity 1 . POI is often seen as an inevitable complication of abdominal surgery, and attempts have been made to reduce the incidence by enhanced recovery after surgery protocols, less opioid use and studies investigating the use of chewing gum 2 . Still, POI is leading to discomfort, impaired recovery, a prolonged length of hospital stay, reoperation and readmission 3,4 .…”
Section: Introductionmentioning
confidence: 99%